(untitled) (Research, Society and Development, 2023)
This article addresses the relationship between the reservation of the possible and access to health in the Brazilian context. The reservation of the possible is a legal principle that allows the State to claim financial limitations to guarantee social rights, such as access to health. In this scenario, we seek to analyze how this notion has impacted the effective access to health services in Brazil, considering public policies and the availability of resources for this purpose. Thus, the objective of this study is to investigate how the concept of reservation of the possible has been used as a justification to restrict access to health in Brazil. Thus, it seeks to understand the impacts of the reserve of the possible on vulnerable groups and the most needy populations that depend on the Unified Health System (SUS). The research is based on a qualitative approach, with bibliographic review and documentary analysis. The research results indicate that the reserve of the possible has often been used as a justification for reducing investments in public health in Brazil. This has had negative impacts on access to health services, especially for the most vulnerable groups in society. Judicial decisions have also been influenced by this principle, which can undermine the realization of the constitutionally guaranteed right to health. In addition, public policies have faced financial challenges, affecting the quality and availability of health services offered by the SUS. In conclusion, the relationship between the reservation of the possible and access to health in Brazil is a complex and relevant issue. The principle has been used as a way to justify the scarcity of resources allocated to health, directly impacting the poorest population. The discussion on the reserve of the possible is crucial to improve the Brazilian health system and ensure effective access to essential services to all citizens.